Integrating Short Stories into English Language Teaching: What English Teacher Educators Say about It? - Gina Oktaviana Oktaviana; Sumardi Sumardi Sumardi; Endang Setyaningsih Setyaningsih (STAI Hubbulwathan Duri, 2022)
Although prior studies have shown the pedagogical potential of short stories in language learning, only a few studies have investigated English teacher educators' perceptions and experiences with short stories in initial language teacher education courses. This narrative study aims to investigate how short stories are integrated into English language teaching in a teaching education institution. Empirical data were gathered through semi-structured interviews with three English teacher educators. This study used member-checking to ensure the validity of the data. Four steps were used to analyze the data in this study: 1) compiling, 2) disassembling, 3) reassembling, and 4) interpreting. Findings showed that the integration of short stories was carried out in two ways. First, short stories were used as teaching materials in extensive reading courses in the second semester. Second, short stories were used as the basis for creating learning activities. Eight classroom activities were identified from English teacher educators’ stories. Three challenges were encountered by English teacher educators in integrating short stories into English language learning, such as finding the “right” short stories, students' low interest in reading the short stories, and limited facilities and time to execute the planned activity. Generally, the findings imply that the selection of short stories appears to be an essential element, and if English teacher educators can successfully overcome the challenges they encounter, the integration process can be smoothly conducted. Hopefully, future studies will provide ways for teachers to select the right stories and develop learning activities based on the stories chosen.